Knockdown of ANGPTL2 Protects Renal Tubular Epithelial Cells Against Hypoxia/Reoxygenation-Induced Injury via Suppressing TLR4/NF-κB Signaling Pathway and Activating Nrf2/HO-1 Signaling Pathway. (28th September 2020) - Xiang, Heli; Xue, Wujun; Li, Yang; Zheng, Jin; Ding, Chenguang; Dou, Meng; Wu, Xiaoyan
Renal ischemia/reperfusion (I/R) injury is a particular threat faced by clinicians in kidney transplantation. Previous studies have confirmed the importance of oxidative stress and inflammation in the pathogenesis of I/R injury. Angiopoietin-like protein 2 (ANGPTL2) belongs to the angiopoietin-like family and has been found to be involved in the regulation of kidney function as well as oxidative and inflammatory response. In the present study, we aimed to evaluate the role of ANGPTL2 in renal I/R injury in vitro . The human proximal tubular epithelial cell line (HK-2 cells) was subjected to hypoxia/ reoxygenation (H/R) to mimic I/R injury in vitro . We found that the expression level of ANGPTL2 was markedly increased in H/R-induced HK-2 cells. Knockdown of ANGPTL2 improved the decreased cell viability of HK-2 cells in response to H/R stimulation. Knockdown of ANGPTL2 significantly inhibited the H/R-caused increase in levels of reactive oxygen species, malondialdehyde, and proinflammatory cytokines, including interleukin (IL)-6, IL-1β, and tumor necrosis factor-alpha, as well as a decrease in superoxide dismutase activity in the HK-2 cells. Besides, the increased bax expression and caspase-3 activity and decreased bcl-2 expression in H/R-induced HK-2 cells were also attenuated by knockdown of ANGPTL2. Moreover, ANGPTL2 overexpression showed the opposite effects. Further mechanism investigations proved that the activation of Nrf2/HO-1 signaling pathway and the inhibition of toll-like receptor 4/nuclear factor kappa-light-chain-enhancer of activated B cells signaling pathway were both implicated in the renal-protective effects of ANGPTL2 knockdown on H/R-induced HK-2 cells. Collectively, these findings suggested that ANGPTL2 might be a new possible target for the treatment and prevention of renal I/R injury.